Sectoral Movement as an Incentive for Interregional Migration - Alexander Kubis (European Regional Science Association (ERSA), 2005)
This work examines the potential connection between migration and sectoral movement. We understand interregional migration as a sustainable relocation of an individual's center of life between two regions. Different quality levels of the boundaries between the regions of the analysed area are considered. Sectoral movement is defined as the relative variation of the regional gross value added in the primary, secondary and tertiary sector. The chosen area to analyse is the Federal Republic of Germany. For the regional classification we use the hierarchic nomenclature NUTS1, provided by the Statistical Office of the European Communities, EUROSTAT. The investigated area consists of the 16 German Federal States. Along with the spatial relationships we analyze the influence of sectoral changes on the flows of migration between these regions during the years 1995 to 2002. The theoretical description of this migration is based on the observations of L.A. SJAASTAD(1962) as well as M.P. TODARO(1969) and J.R. HARRIS / M.P. TODARO (1970), who considered migration as a result of individual decisions due to a sophisticated complex process. Migration as an individual investment in human resources raises the question about the specific costs for an emigrant's human resources stock. When emigrating to a region, where he finds an adequate work, the emigration costs are lower. His tendency to migrate should hence be in accordance with the corresponding sectoral supply of employment. Therefore, we investigate the hypothesis, whether the tendency to migrate increases, if the sectoral gross value added of a region i rises relatively to a region j.
Keywords: 330